Agricultural economics and agribusiness - Cramer, Gail L. (Wiley, 1994)
Featuring complete coverage of agribusiness, this edition has been revised and updated to include a new section on GATT. It also examines the economic changes taking place in the former USSR and mainland China, and the effects of the North American Trade Alliance on agribusiness.